TOKSISITAS AKUT BANDOTAN (Ageratum conyzoides ) TERHADAP MORTALITAS KUMBANG JAGUNG (Sitophilus zeamais Motschulsky) - Dian Mutiara Ita Emilia (Universitas PGRI Palembang, 2013)
Investigation about Acut Toxicity of Bandotan Leaf ( Ageratum conyzoides) to Mortality Maize Weevil (Sitophilus zeamays) was conducted on Juni – September 2013 in laboratory Biology Faculty of Mathematic University of PGRI Palembang. Acut tocxicity test using the maize weveil bioassay method with a time of 96 hours aplication. The shows that results that leaf of Bandotan were toxic to maize weevil whith 24 hours, 48 hours and 96 hours LC 50 were 29.279 %, 21.610 % and 16.477 %. Key words ; Toxicity. Ageratum conyzoides, Sitophilus zeamais M.). LC50